Adaptive gait algorithm for the MOBOT quadruped - Villorente, Gabriel Fojas
Legged Robots offer a high adaptability with intricate maneuverability over an irregular terrain. This study implements an adaptive gait algorithm as the central gait generator based on the status of each leg. Part of the algorithm was tested using the four-legged robot platform developed in the Mobile Robotics Laboratory, University of the Philippines Diliman. This platform was deployed with a forward priority in a configurable structured terrain with steps, slopes, and rectangular obstacles.